EFFICIENCY OF SYNTHETIC INSECTICIDES FOR THE MANAGEMENT OF APHID, MYZUS PERSICAE (SULZER) ON MAIN POTATO CROP IN WESTERN INDO-GANGETIC PLAINS - Khajuria, Shakti; Malik, Kamlesh (Potato Journal, 2013)
Potato aphid, Myzus persicae Sulzer (Aphididae;Hemiptera) causes considerable damage to many crops in various parts of the world, both by direct feeding and by virus transmission. The problem is aggravated by their role as vectors of several viruses, which, although seldom lethal, reduce plant vigour and yield potential of seed tubers. During 2002-2004, field studies were carried out to evaluate the effects of different insecticides for the management of Myzus persicae in main potato crop with cultivar Kufri Badshah at Modipuram. The research trial was laid out in RBD with seven treatments and a check plot was also maintained for comparison. Aphid population was estimated by counting live individuals on the upper, middle and lower leaves of 11 plants/plot at weekly intervals after one month of planting. The emergence of pest on the crop in both the years occurred during 2nd week of December, which crosses the critical level i.e., 20 aphids/100 leaves in the 3rd /4th week of December. The efficiency of insecticides was assessed by counting the aphids mortality on treated plots. During 2002-2003, potato planted on October 18, 2002 efficacy of Phorate 10G application at the time of earthing up 1.0kg a.i/ha; imidacloprid @ 0.01% and 0.02%; Metasystox 25EC (oxydemeton methyl) @ 0.015%, 0.03%, and 0.05%. The population reduced in these treatments after spraying (December 19, 2002). Data suggested that imidacloprid @ 0.02% was the best for the management of M. persicae followed by imidacloprid @ 0.01%, metasystox 25EC @ 0.05%, 0.03% and 0.015%. In control, the population continued to buildup as 3.75, 17.0, 29.0, 38.0, 45.0, 87.0 and 74.0 M. persicae/11 plants monitored from second week of December to last week of January. In the year 2003-04, crop was planted on October 21, 2003 using same cultivar and the efficacy of Phorate 10G @ 1.0kg a.i/ha; Imidacloprid @ 0.01%, 0.02% and 0.03%; cow urine @ 50ml/litre and table salt(Sodium chloride) @10gm/litre of water. The results revealed that imidacloprid @ 0.03% gave the highest over all mortality against aphid population. Imidacloprid @ 0.02% gave the second highest mortality followed by imidacloprid 0.01%. Cow urine and salt did not show consistency in its effectiveness and was not very much effective against this pest. In the untreated plots aphids population growth was continued with out any interference. It was observed that all the tested insecticides controlled aphids population, yet imidacloprid proved to be the most effective.